PERANCANGAN DISPLAY INFORMASI KETERSEDIAAN BLANKO KTP ELEKTRONIK DINAS DUKCAPIL KABUPATEN LOMBOK TIMUR - Sri Handriana Dewi Hastuti (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2021)
The need for information is increasingly high in the era of growing technology. The delivery of information quickly and actual becomes a challenge in developing an information technology. One type of public service that is the government's obligation and has a strategic role is public services in the field of population and civil registration. People are sometimes disappointed when they want to get population administration services, especially Electronic Identity Cards. By not announcing the availability of physical blank stocks of Electronic Identity Cards, intermediaries can use them in managing population administration. On the pretext that the physical blank of the Electronic Identity Card is used up, so that it can be used as a moment for intermediary individuals to seek profits in managing population administration. With this electronic Blank Information Display, it is hoped that the public will obtain information disclosure regarding available blank Electronic Identity Cards.